Black Holes and termic field dynamics - Ruiz, Jhonny; Ferreira, Alesandro (Cadernos de Astronomia, 2026)
Work presented at ’The Astro-scientists: III Brazilian Meeting of Girls and Women in Astrophysics, Cosmology, and Gravitation,’ held between March 31 and April 4, 2025.
Keywords: black holes; quantum field theory; temperature